The comparison of sexual function in types I and II of female genital mutilation - Kosar Hassannezhad; Firouzeh Asadzadeh; Sohrab Iranpour; Soheila Rabiepoor; Pouran Akhavan Akbari (BMC, 2024)
Abstract Background Female genital mutilation has many sexual, physical, and psychological consequences. The present study aimed to examine the relationship between Female Genital Mutilation/Cutting (FGM/C), and Sexual Function among circumcised women in Sardasht City, Iran." Methods In this present cross-sectional study, 197 women who were mutilated entered the study by simple random sampling from two healthcare centers in Sardasht, Iran. A gynecologist first performed a genital examination to identify the type of female genital mutilation of participants. Subsequently, Socio-demographic and FGM/C-related characteristics checklist and the female sexual function index questionnaire were completed by interview method. Data were analyzed using SPSS 23 software. Results Type I and II of female genital mutilation were performed in 73.1 and 26.9% of the participants, respectively. The age range of performing female genital mutilation in type I and II of female genital mutilation was 4-10 years old in 67.4% and 71.1% respectively. Traditional practitioners/local women carried out the circumcision in all of the participants, and Sunnah/tradition was reported as the most common reason for doing this procedure. The average total score of FSFI index in type I and II of female genital mutilation was 23.5 ± 2.0 and 17.4 ± 2.39, respectively. In all domains of FSFI, women with type II of female genital mutilation obtained lower scores than women with type I. Conclusion Circumcised women have reduced scores in all domains of FSFI, and the severity of sexual dysfunction is related to the type of FGM/C. Considering the prevalence of female genital mutilation and its adverse effects, it is imperative to initiate cultural improvements through education and awareness. By educating and raising awareness among individuals about this issue, we can foster positive changes and address the problem effectively.